1997
DOI: 10.1093/humrep/12.11.2528
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal interleukin-10 increases with decrease in activated CD4+ T lymphocytes in women with endometriosis

Abstract: This study was performed to determine whether peritoneal T cells are suppressed in the CD4+ or CD8+ T cell subpopulation and whether they are Th1 or Th2 predominant in women with endometriosis. Immune cells in the peritoneal fluid (PF) were obtained from women undergoing laparoscopy for endometriosis or tubal ligation. Three-colour flow cytometry was utilized for immunophenotyping of peritoneal fluid mononuclear cells (PFMC). Concentrations of interleukin (IL)-4, IL-5 and interferon-gamma (IFN-gamma) produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 0 publications
3
59
1
2
Order By: Relevance
“…There are many conflicting reports in the literature on the analysis of the action of each cytokine in endometriosis and the clinical application of the results obtained with the measurement of these cytokines for the laboratory diagnosis of endometriosis. Punnonen et al (1996), Ho et al (1997) and Tabibzadeh et al (2003) also observed an increase in IL-10 in the peritoneal fluid of patients with endometriosis. On the other hand, in a study carried out in patients submitted to IVF, the authors concluded that IL-10 was higher in the control group comprised of fertile patients than in women with endometriosis and also in fertile patients than in women with infertility of inapparent cause, proving that Th2 response facilitates trophoblastic implantation at the beginning of pregnancy (Ginsburg et al, 2005).…”
Section: Discussionmentioning
confidence: 75%
“…There are many conflicting reports in the literature on the analysis of the action of each cytokine in endometriosis and the clinical application of the results obtained with the measurement of these cytokines for the laboratory diagnosis of endometriosis. Punnonen et al (1996), Ho et al (1997) and Tabibzadeh et al (2003) also observed an increase in IL-10 in the peritoneal fluid of patients with endometriosis. On the other hand, in a study carried out in patients submitted to IVF, the authors concluded that IL-10 was higher in the control group comprised of fertile patients than in women with endometriosis and also in fertile patients than in women with infertility of inapparent cause, proving that Th2 response facilitates trophoblastic implantation at the beginning of pregnancy (Ginsburg et al, 2005).…”
Section: Discussionmentioning
confidence: 75%
“…In peritoneal fluid of women with endometriosis, decreased natural killer (NK) cell activity (Oosterlynck et al 1991;Ho et al 1995), dysfunction of T lymphocytes (Ho et al 1996;Szyllo et al 2003), infiltrating macrophage (Bacci et al 2009) as well as aberrant concentrations of immune-related cytokines (Ho et al 1997) have been reported in the past two decades. Thus, it has been proposed that an impaired immunological clearance of endometrial fragments shed into the peritoneal cavity may facilitate the implantation of endometrial cells in ectopic locations and result in endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…We noted a significant mcrease in level of IL IO in peritoneal fluid and serum from women with endometriosis than in the control group. Recently studies also demonstrated an elevated level of this cytoidne in peritoneal fluid of women with endometrio.sis (34,35). In addition to this, the higher amounts of IL-10 in peritoneal fluid of women with ev\domett\osis conelaved IL-10 t\hoTO-cleic acid (mRNA) expression in the cells presented in peritoneal fluid of affected women (36).…”
Section: Discussionmentioning
confidence: 92%
“…The most Immunologie changes observed in this study were noted in the early stage of endometriosis, but not in the advanced stage of the disease. Other studies also indicated increased production of IL-10 by peritoneal macrophages of women with early endometriosis rather than in stage III and IV of endometriosis (34,39,40). However, no differences in ihe amounts of IL-10 in either peritoneal fluid or peripheral blood from women with superficial and dceply inllltrating endometriosis were also reported (36,41).…”
Section: Discussionmentioning
confidence: 96%